1998
DOI: 10.1101/gad.12.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and developmental control of O2 homeostasis by hypoxia-inducible factor 1α

Abstract: Hypoxia is an essential developmental and physiological stimulus that plays a key role in the pathophysiology of cancer, heart attack, stroke, and other major causes of mortality. Hypoxia-inducible factor 1 (HIF-1) is the only known mammalian transcription factor expressed uniquely in response to physiologically relevant levels of hypoxia. We now report that in Hif1a −/− embryonic stem cells that did not express the O 2 -regulated HIF-1␣ subunit, levels of mRNAs encoding glucose transporters and glycolytic enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

61
1,747
8
27

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,260 publications
(1,876 citation statements)
references
References 60 publications
61
1,747
8
27
Order By: Relevance
“…Furthermore, ARNT -deficient embryos have decreased VEGF mRNA and protein levels, which implies that VEGF secretion is modulated by naturally low O 2 microenvironments in the early conceptus [22][23][24] . Consistent with these findings, Iyer et al demonstrated that HIF-1α protein can be detected in E8-E18 mouse embryos 25 ; HIF-1α -deficient embryos show similar phenotypes to Arnt −/− mice, with defects in blood vessel formation and neural fold closure 25,26 .…”
Section: Mammalian Cardiovascular Morphogenesis Is Regulated By Hifmentioning
confidence: 76%
“…Furthermore, ARNT -deficient embryos have decreased VEGF mRNA and protein levels, which implies that VEGF secretion is modulated by naturally low O 2 microenvironments in the early conceptus [22][23][24] . Consistent with these findings, Iyer et al demonstrated that HIF-1α protein can be detected in E8-E18 mouse embryos 25 ; HIF-1α -deficient embryos show similar phenotypes to Arnt −/− mice, with defects in blood vessel formation and neural fold closure 25,26 .…”
Section: Mammalian Cardiovascular Morphogenesis Is Regulated By Hifmentioning
confidence: 76%
“…When this occurs, HIF-1α complexes with HIF-1β, translocates into the nucleus and binds to a specific sequence in the 5′ flanking region of the VEGF gene, the hypoxia responsive element (HRE) (Ikeda et al, 1995;Laughner et al, 2001;Shima et al, 1996;Wenger, 2002;Forsythe et al, 1996). The importance of interaction between HIF-1α and the VEGF promoter has been confirmed in studies of HIF-1α −/− mouse embryonic stem cells, in which basal expression of VEGF mRNA remains low in response to hypoxia (Carmeliet et al, 1998;Iyer et al, 1998).…”
Section: Regulation Of Vegf Expressionmentioning
confidence: 98%
“…In the dimeric, active state, HIF-1 and HIF-2 bind to hypoxia responsive elements (HREs) located in genes regulated by hypoxia and HIFs. Although HIF-1 and HIF-2 seem to activate hypoxiaresponsive genes by similar means (Tian et al 1997;Wiesener et al 1998), the HIF-α subunits work in a non-redundant manner and several differences in gene regulation have been proposed, many of which emphasize the predominant role of HIF-1 in regulating the transcriptional response to hypoxia (Iyer et al 1998;Ryan et al 1998;Hu et al 2003;Park et al 2003;Sowter et al 2003). As detailed below, HIF-2 is also crucial for the hypoxic response, and, as opposed to HIF-1, it is active at prolonged hypoxia as well (HolmquistMengelbier et al 2006).…”
Section: Introductionmentioning
confidence: 99%